Validitas Teoritis Panduan Bimbingan Klasikal Peningkatan Social Awareness untuk Pencegahan Sexting Remaja - Wibowo, Shinta Gandha; Hidayat, Rian Rokhmad; Suryawati, Citra Tectona (Jurnal Psikoedukasi dan Konseling, 2024)
This study aims to develop a guideline for classroom guidance services that aims to increase social awareness as a measure to prevent sexting among high school students in Sukoharjo regency. The theoretical validity test in this research uses a modification of the ADDIE R&D model, which consists of three stages: analysis, design, and development. This research is limited to the development stage, which includes data collection, guidelines development, self-help development and assessment by guidance and counseling experts. The developed module has received a high validity rating from two guidance and counseling experts. The results of this assessment indicate that the product being developed meets the criteria for theoretical validity and is ready to be assessed in terms of its practicality and effectiveness. Further research can be carried out by making improvements to the guidelines developed in this study, by continuing to the implementation and evaluation stages.